The relationship between external presssure and socio-environmental disclosure in the integrated reports of South African Banks - Mchavi, Nyiko D. (My University, 2017)
This research evaluated the role of external pressure on the sustainability of South African banks. Although much research on corporate sustainability disclosure has been done, this research is important since little of the previous research in South African has given a closer examination to sustainability external pressure implication of external pressure on banking sector sustainability disclosure. In addition, this research separated banks’ sustainability disclosure into social and environmental aspects to know which aspect in the banks are more influenced by external pressure. Therefore, the main objective of this research was to examine the relationship between external pressures on social disclosure and to examine the role of external pressure on environmental disclosure in select South African banks. Although the entire commercial banks in South African made up the population of study, the sample was reduced by the availability of external pressure variables (government pressure, political pressure, social pressure, regulatory pressure, customer pressure, and two control variables – reputation and profit objectives) in the sustainability reports within the six years of study (2010 – 2015). Research data were collected from secondary data which were available from the annual integrated reports of banks. Data were analysed by means of the panel data multiple regression analysis. The analysis of data on research question 1 showed that three independent variables (Government pressure, profit objective and customer pressure) showed a significant positive relationship with social disclosure. Government pressure showed a significant relationship at a value of P=0.006 which is less than the 0.05 alpha level set for this research. This therefore means that within the sample of banks where data were collected, government pressure have a significant positive relationship with social disclosure in these banks. Also, the analysis showed that profit objective and customer pressure are positively and significantly related to social disclosure at a value of P=0.05 which is equal to the alpha of this research. This also means that within the sample of banks where data vi were collected, profit objective and customer pressure have a significant positive relationship with social disclosure in these banks. On the contrary, four out of the seven independent variables (regulatory pressure, political pressure, social pressure and reputation) showed no significant relationship. The second research question in this study was to find whether a relationship exists between external pressure and environmental disclosure. However, all the independent variables showed a non-significant relationship with environmental disclosure. In conclusion, the research made some recommendations which include that future researchers should expand the number of banks by including other financial institutions, the comparison of sustainability disclosure in banks before and after the King III report, more improved teaching and research on banking sector sustainability disclosure in higher institutions, communication of research result such as on banking industry sustainability to practitioners and to government agencies. Other recommendations include the need to conduct a regional study to include other African countries on banking sector sustainability and to conduct a survey study on external pressure on banking sector environmental activity and disclosure
Thesis (M. Com. (Accountancy)) -- University of Limpopo, 2017
Keywords: Social disclosure; Environmental disclosure; Sustainability disclosure; South African banks; King III; External pressure; Banks and banking -- South Africa; Corporation reports -- South Africa; Sustainability; Social responsibility of business -- South Africa; Social responsibility in banking